The Effectiveness of Team-Based Learning Integrated with Canvas LMS in Enhancing Students’ Reading and Critical Thinking Skills - Nurul Khasanah; Rudi Hartono; Puji Astuti; Sri Wahyuni (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This research investigates the effectiveness of the implementation of Team-Based Learning (TBL) combined with technology, in this case is the Canvas Learning Management System (Canvas LMS), to improve reading skills and critical thinking skills among students from English as a Foreign Language (EFL) classrooms. Using a quasi-experimental design, the study involved 112 third-semester students in Critical Reading courses. The sample was determined through cluster random sampling, which consisted of a C class that consisted of 28 students of the English Department in the State Islamic Institution of Ponorogo. Pre-test and post-test were administered, and data were analyzed using a paired sample t-test. The findings showed a significant enhancement in reading skills due to the integration of Canvas LMS into TBL (sig = 0.000 < 0.005), as evidenced by the increased scores on the mean scores of pre-test and post-test from 62.57 to 80.61. Students also showed an increase in their critical thinking skills. The implications of these findings provide further insights into the effectiveness of integrating TBL with the use of technology to improve academic reading and critical thinking in EFL settings and a suggested strategy for developing such essential skills in university contexts.